The health of black elderly people from religions of African origin in the combined prevention of HIV/AIDS/STIs - Batista, Maria Amanda Lima; Araújo, Kadja Elvira dos Anjos Silva; West, Milka Gabrielle de Lira Nobrega; Araújo, Ednaldo Cavalcante de; Pereira, Danilo Martins Roque; Nascimento, Joana Pereira Medeiros do; Silva, Liniker Scolfild Rodrigues da; Oliveira, Thainara Torres de; Carvalho, Pablo Ramon da Silva; Sousa, Josueida de Carvalho (Seven Editora, 2024)
Combined HIV prevention strategies using condoms and lubricant gel for full use in all sexual practices have a biomedical character because they are methods of physical barriers and a behavioral and structural approach. When they are adopted by black elderly women, who are inserted in a context of vulnerability imposed by society, the structural character comprises a set of violence and oppressions, such as machismo and racism, which make it difficult and often prevent them from using these inputs. The aim of this study chapter is therefore to highlight aspects of the health of black people from religions of African origin in combined HIV/AIDS/STI prevention. It is hoped that making this knowledge available will help improve the quality of health care for black elderly people from Ilê by analyzing the bias of practicing safe sex with the use of condoms and lubricant gel. DOI:https://doi.org/10.56238/sevened2023.007-013